Capital malleability and the macroeconomic costs of climate policy - Elisa Lanzi; Ian Sue Wing (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper argues for introducing the role of capital malleability into the analysis of environmental policies. The issue is explored by means of a theoretical model, a numerical analysis and a computable general equilibrium (CGE) model. Considering the three approaches together is fundamental in obtaining theory-compatible policy-relevant results. The model outcomes reveal differences between results under separate assumptions regarding the malleability of capital. When capital is imperfectly malleable a carbon policy is less effective than under the assumption of perfect malleability of capital. Therefore, it is important that, especially for the analysis of short-term environmental regulations, the issue of capital malleability is taken into consideration.
Keywords: C68; D58; H22; Q43; 330; General Equilibrium; CGE Models; Climate Change Policy; Kapital; Kapitalmobilität; Klimaschutz; Umweltabgabe; Allgemeines Gleichgewicht; CGE-Modelling